(untitled) (Journal of Hama University, 2019)
The Properties of Sub-grade (Support Soil) which road engineer faces_ especially its endurance capacity _ determines thicknesses of pavement layers which carry them, and provide a consistent foundation for the Road. In this research, we studied the potentiality of improving the performance of Sub-grade by improving its physical and mechanical features using the dust caught by means of special filters during cement manufacturing process. A return of electrostatic raw materials mill filter (REMF) _at Hama cement factory_ was added to samples of Sub-grade by three rates (5, 10, 15)% from dry sample weight. And Laboratory experiments were performed to determine these characteristics on the treated samples using return of filter (REMF), and to compare the results of the same experiments on the reference samples from Sub-grade (Support soil). The research concluded that adding the return of filter to Sub-grade (Support soil) improved its performance and Plasticity index decreased by 14%. Furthermore, endurance capacity also increased at good rates depending on adding (REMF) indicated by the (CBR) values ​​recorded in two stages: the first is till the stability of swelling is proved(from 8.3 to 10.8), and the second is immersion for 7 days (from 6.7 to 10.5). So that, the value of (CBR) increased up to 55%. It was found that the addition of (REMF) at 15% of the dry weight of the Support soil samples were optimal ratios for improved performance.